Pelatihan Penyelesaian Soal-Soal Olimpiade Fisika bagi Guru Pembimbing OSN dan Siswa Peserta OSK - Nurfitra Yanto; St. Mutia Alfiyanti Muhiddin; Hasanuddin Hasanuddin; Nurul Muthmainnah Herman (JKM: Jurnal Kemitraan Masyarakat, 2023)
OSN problem is a problem that has a fairly high level of difficulty. OSN problem solving training aims to provide training to OSN guidance teachers and students who want to improve their ability to solve OSN problems. This training was held for two days. On the first day, the service team explained the characteristics of OSN questions and participants were asked to answer practice questions to measure the participants initial abilities, then continued the discussion. The second day the participants did a simulation and continued the discussion. The simulation is aimed at measuring the final ability of participants after training. From the results of the exercises and simulations, it is known that the OSN problem solving training was successful because the number of problems that could be solved by the participants increased. In addition, it was also obtained that the problem material that can be solved by participants is more diverse at the time of simulation than at the time of exercise. This means that participants, especially students who are appointed to represent schools in the OSK 2023 event, are better prepared than before the training.